Analysis of risks at the decision in investment projects ("Journal "U". Economy. Management. Finance.", 2017)
Discusses the need for detailed risk analysis in the process of evaluating the economic efficiency of the investment project. Different approaches when making decisions.
Keywords: investments; investment project; investment risks; evaluation of effectiveness; process of decision-making